Expanding airport capacity under constraints in large urban areas: Summary and conclusions - David Thompson; Stephen Perkins; Kurt Van Dender (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2013)
Expanding airport capacity is difficult in large urban areas. Expansion of existing airports is usually constrained by community agreements on noise and local air pollution and by a shortage of land. Finding sufficient land, at feasible prices, to develop or relocate major airports on green-field sites within a reasonable distance of city centres is often very difficult. Creating land for airports in locations less sensitive to noise and land-use conflicts, for example through offshore or estuarine land reclamation, is expensive and most new sites will require extensive investments in surface transport links to city centres. Furthermore, moving an airport imposes costs on airlines and their users as well as on activities located close to and dependent on proximity to the existing one. In multi-airport regions, options for expansion at one airport will impact the others and airlines, operating in increasingly competitive markets, may respond differently to alternative ways in which the region's airport capacity might be increased.
Keywords: 330